ANALISIS PENDAPATAN ASLI DAERAH KABUPATEN MAMUJU UTARA PERIODE TAHUN 2004-2013 - Mahyuddini, Mahyuddin (Katalogis, 2015)
This study aims to: (1) to acknowledge and analyze the achievements of Local Revenue (PAD) North Mamuju regency year period from 2004 to 2013; and (2) To determine and analyze the financial condition of local government district of North Mamuju dependency ratios in terms of regional financial and local self-reliance ratio to achieve financial independence of North Mamuju regency over the period 2004-2013. There are several tools of analysis are used in this study, such as, trend analysis, regional financial dependency ratio (RKKD), and the regional financial independence ratio analysis. The results provide the conclusion that: (1) The achievement of the locally generated revenues of the North Mamuju regency in the period between 2004 and 2013 experienced a growth trend in each year; and (2) the financial condition of the North Mamuju government in order to achieve financial independence for the period 2004 to 2013 was assessed by the assessment criteria are in a good financial condition. It gives the sense that the level of dependency of the North Mamuju government regency to the central government aid is low, marked with a small proportion of their locally generated revenue (PAD) to the regional fund balance.